Drugs targeting SIRT1, a new generation of therapeutics for osteoporosis and other bone related disorders?. (May 2019) - Zainabadi, Kayvan
Graphical abstract: Abstract: With an aging population and limited treatment options, osteoporosis currently represents a significant public health challenge. Recent animal studies indicate that longevity-associated SIRT1 may serve as an attractive pharmacological target for the treatment of osteoporosis and other bone related disorders. Pre-clinical studies demonstrate that mice treated with SIRT1 agonists show protection against age-related, post-menopausal, and disuse models of osteoporosis. Conversely, SIRT1 knockout models display low bone mass phenotypes associated with increased bone resorption and decreased bone formation. This review summarizes recent animal and human experimental data showing that pharmacological activation of SIRT1 may act in a manner that current treatments do not, namely by treating the imbalance in bone remodeling that is the root cause of osteoporosis and other bone disorders.